A relação entre a educação e o trabalho na educação profissional técnica de nível médio do IFG – câmpus Goiânia: contradições, impasses e perspectivas - Guimarães, Gilda (2017)
The thesis The relationship between education and work in the technical secondary professional education of the IFG – Câmpus Goiânia: contradictions, impasses and perspectives resumed the Institution's trajectory in technical and secondary education between 1986 and 2015. The main objective of the research is to understand the dynamics, characteristics and determinants of professional education at IFG – Câmpus Goiânia, inquiring if the Institution was constituted and remains as a possibility for the integral formation of young people, besides the functionality of the immediate preparation for the labor market. When we reflected on the proposed questioning, we sought to recover the elements of integration and disintegration of professional education with the processes of secondary schooling as the final stage of basic education in Brazil. The research started from the understanding of the work as an educational principle by the ontological and historical dimension that it assumes as a human praxis, constituent and constitutive of man as a social subject, but also as a process of subjection and alienation of man in the context of capitalist relations of production. In the perspective of the analysis of transformations in the world of work and production, the studies of Marx (1996a and 1996b), Gramsci (2011), Harvey (1993), Santos (1998), Mészáros (2008), among others, oriented the theoretical investigation of this research. In the analysis of the process of insertion of Brazil in the logic of production and reproduction of capital in local and world terms, as well as its developments in the field of professional education, we highlighted the contributions of authors such as Fernandes (1976), Cunha (2005), Germano (1990), Frigotto and Nosella, the latter ones with a research track and several publications about the relationship between education and work in the organization of the school system and the policies of basic and professional education in Brazil in the period noticed by the research. This is a qualitative research, characterized as a case study, based on interviews with professors from IFG – Câmpus Goiânia, developed under the Education, Work and Social Movements line of the Graduate Program in Education of the Federal University of Goiás. The hypothesis that the tension and asymmetry inside the structures and actions, in the levels and modalities of education, tend to detail the performance of the Institution in the integrated technical education was evidenced. However, the interviews with the teachers showed that the rooting of the IFG – Câmpus Goiânia in basic secondary education finds strong ties of defense by the affirmation of the offer of the technical courses as a possibility of school formation, in the limits of the contradictions and clashes around the policies, projects and educational practices of the Institution.